(untitled) (The Pakistan Development Review, 1974)
Of the several approaches designed to study the adoption of family plann¬ing methods one approach emphasizes the dynamics related to the husband-wife dyad, especially communication and interaction between the spouses as related to family planning behaviour. Interspousal communication has been shown to be an important variable in family planning behaviour in relatively underdeveloped as well as developed societies. Authors of the well-known Puerto Rican family study attributed a great deal of importance to interspousal communication as an explanatory factor in family planning and fertility behaviour [5 and 6]. Hill [6] described communi¬cation as the "hub" variable and concluded that the principal factors in family planning adoption were emphasis on planning, communication between spouses and the ability to come to a joint decision. Using data from a survey in East Pakistan (now Bangladesh), Green [3] showed that contraceptive use was correlated directly with interspousal com¬munication. Among non-user couples, 75 % of the husbands and 69 % of the wives said they had learned nothing from their spouses, compared with only 45% and 17% of user husbands and wives saying they had learned nothing from each other. Green feels that one of the major barriers to diffusion of action-associated knowledge about family planning is the lack of communication between spouses.